Pengembangan Media Pembelajaran Berbasis Mobile Learning Pada Mata Pelajaran Dasar Listrik Dan Elektronika Sekolah Menengah Kejuruan - Mery Sumiati; Fahmi Rizal; Muhammad Anwar (Universitas Negeri Padang, 2020)
In the learning process Basic Electricity and Electronics material, students are constrained in understanding the subject matter, because it uses formulas that are difficult to understand without adequate supporting learning media. Besides the learning time Basic Electricity and Electronics material which is only available 4 hours per week, so that not all materials can be delivered optimally to students. Therefore learning needs to be supported by suitable and adequate media. The purpose of this research is to produce a learning media based on mobile learning that is valid, practical and effective for Basic Electricity and Electronics subjects. The method used in this research is Research and Development (R&D). The development model used follows the Borg & Gall model which is arranged in several research steps. The instrument used in the form of a validation questionnaire was given to material experts and media experts. Questionnaire to measure practicality is given to students and teachers of the subject matter. To measure the effectiveness of the Quasi experiment research design used by comparing student learning outcomes of the experimental class and the control class. The results showed that the learning media based on mobile learning was declared valid, practical and effective for use in the Basic Electricity and Electronics subjects.